THE EFFECT OF PUPPET SHOW ON HOSPITALIZATION IN PRESCHOOL CHILDREN (3-6 YEARS) - Sulpat, Emuliana; Mardhika, Amellia; Fadliyah, Lailatul; Tyas, Anestasia Pangestu Mei; Harianto, Susilo; Ilhami, Yusrina Ika (Universitas Airlangga, 2022)
Introduction: One way to minimize the impact of hospitalization is storytelling with dolls or puppet shows , which is a type of game using puppet media through fantasy games for preschoolers (3-6 years old). The purpose of this study was to determine the effect of play therapy